Risky Behavior In Teenagers Dating Senior Secondary School (SLTA): Studies in the Central Java city of Blora - Teguh Wahyudi; Agus Prasetyo; Tavip Indrayana (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
This study aims to analyze the factors that influence the risky dating activities among teenagers at senior high school in Blora, Central Java. A descriptive correlational design was employed and all data were collected using cross-sectional approach. A total of 180 samples were selected by proportional random sampling technique and all data were collected using questioners. Study results showed that there were 21 respondents (11.7%) doing petting and 15 respondents (8.5%) doing intercourse during dating. Independent variables that correlate with the risky dating activities among teenager were attitude toward risky dating (χ² = 10.881, p=0.001), the presence of friends who agree that love can be manifested by sexual activities (χ² = 9.274, p=0.002), the presence of friends who have loose behaviours in premarital sexual activity (χ² = 12.650, p=0.000), the presence of friends who told about the fun of performing sexual intercourse during dating (χ² = 10.271,p=0.001) and the presence of friends that ever doing premarital intercourse (χ² = 8.020, p=0.005). The school also needs to conduct reproductive health counseling to cultivate the right attitude about risky dating. It is also suggested that relevant agencies should take action to optimize the rules about pornographic restrictions in the interned cafes.